Gunung Api Lumpur di Daerah Cengklik dan Sekitarnya, Kabupaten Boyolali Provinsi Jawa Tengah - Bronto, Sutikno; Asmoro, Pudjo; Efendi, Mutiara (Jurnal Geologi dan Sumberdaya Mineral, 2017)
District of Boyolali and surrounding area have manifestation of an old mud volcano deposits which is locally exposed in E-W direction, about 20 km length and 3-5 km wide, start from Cengklik Lake until western side of Solo River. The mud volcano deposits have clay-silt size and sand-gravel of scoriaceous basaltic andesite in Gununglondo village. Materials below the mud deposits are composed by dike or sills-like rocks which penetrate within the sediment layer and fill the fracture formed a diapiric and mud ball structure, whereas the loss materials tend to leave diatremal traces and surficial deposits. Data showed in this research illustrate the mud movement from subsurface to the earth surface which is comparable with volcanic eruptions. After reaching the surface, mud deposits form layers with some slight folded and faulted structure. Cengklik Lake depression is presumed to be paleo mud volcano crater. Cengklik and surrounding areas are rapidly develop due to the existence of Adisumarmo international airport and construction of Solo-Semarang–Surabaya toll road. Considering the geological condition below Cengklik and surrounding area, which is composed by mud volcano deposits and experienced many fracture, they assumed to be a weak zone. The main potential geological hazard is the surface deformation along the toll road because of its low capability to endure the road construction and vehicle weight. Other potential hazards are groundwater pollution, earthquake, and mud volcano reactivation. Therefore, sustainable research and geological hazard mitigation of Cengklik and surrounding areas are necessary to do. keywords: mud volcano, Cengklik, Boyolali, geological hazards, mitigation